Nitroxyl anion – the universal signalling partner of endogenously produced nitric oxide? - Martin, William (Blackwell Publishing Ltd, 2009)
Although it is generally assumed that the primary product of the three isoforms of NO synthase is the nitric oxide radical (NO(•)), growing evidence suggests that the one-electron reduced form of nitrogen monoxide, nitroxyl anion (NO(−)), may be a natural co-product. Thus, evidence from conduit and resistance arteries and nitrergically innervated tissues indicates that NO(−) exerts widespread signalling functions alongside NO(•) in the cardiovascular and autonomic nervous systems, and perhaps beyond. In this issue of the BJP Andrews et al. add to this debate by providing strong evidence that NO(•) and HNO both contribute to the EDRF-mediated component of in mouse (MMA) and rat (RMA) mesenteric resistance arteries. British Journal of Pharmacology (2009) 157, 537–539; doi:10.1111/j.1476-5381.2009.00153.x This article is a commentary on Andrews et al., pp. 540–550 of this issue and is part of a themed section on Endothelium in Pharmacology. For a list of all articles in this section see the end of this paper, or visit: http://www3.interscience.wiley.com/journal/121548564/issueyear?year=2009